Organic formazan-based corrosion inhibitor for carbon steel in acidic medium: A synergistic experimental and theoretical study - Luay Ali Khaleel; Oraas Adnan Hatem; Duhak Ahmed Alwan (Results in Chemistry)
This study presents the synthesis, characterization, and corrosion inhibition potential of a novel formazan derivative derived from a Schiff base precursor, offering a promising approach for carbon steel protection in acidic environments. The Schiff base was synthesized via the reaction of 4-aminoantipyrine with 4-(dimethylamino) benzaldehyde, followed by the generation of the formazan derivative through diazo coupling with a diazonium salt, prepared from 1-amino-2-hydroxy-4-naphthalene sulfonic acid in an acidic medium HCl, (0–5)°C. Structural characterization was conducted using Fourier-transform infrared spectroscopy (FT-IR), proton nuclear magnetic resonance (1H NMR), and carbon nuclear magnetic resonance (13C NMR) to confirm the successful formation of the target compound.The corrosion inhibition efficiency (IE%) of the synthesized formazan derivative was systematically evaluated on carbon steel in 1 M HCl at varying concentrations (5 × 10−5 M to 1 × 10−2 M) and temperatures (20 °C to 50 °C). The inhibitor demonstrated a remarkable efficiency increase from 53.6 % at 5 × 10−5 M to 91.5 % at 1 × 10−2 M at 20 °C, with electrochemical analyses confirming its mixed-type inhibition behavior, affecting both anodic and cathodic reactions.To gain deeper molecular insights, quantum chemical calculations (PM3 method) were employed, revealing that protonation of the formazan derivative significantly modulates its electronic properties, reducing the energy gap and chemical hardness while enhancing chemical softness and electrophilicity. These findings suggest that the protonated form exhibits superior charge transfer capabilities, facilitating strong interactions with the carbon steel surface and contributing to its inhibition efficiency.